2021
DOI: 10.1186/s42523-021-00114-3
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of “papillomavirome” in bovine teat papilloma lesions

Abstract: Background Papillomaviruses are small nonenveloped, circular double-stranded DNA viruses that belong to the Papillomaviridae family. To date, 29 Bos taurus papillomavirus (BPV) types have been described. Studies involving mixed BPV infections have rarely been reported in contrast to human papillomavirus (HPV), which is commonly described in numerous studies showing coinfections. Moreover, previous studies had shown that HPV coinfections increase the risk of carcinogenesis. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…These results were similar to the present study, where teat wart lesions were found in 13.6% of the examined cows (from which more than one third were positive using PCR amplification). Epidemiological studies provided on cattle in Germany, Italy and Turkey reported ten types of BPV (1,2,3,4,6,7,8,9,10,11) [39][40][41][42][43]. In our study, types 1, 3, 6 (mostly related to teat papillomatosis) and 11 were not detected in examined samples.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…These results were similar to the present study, where teat wart lesions were found in 13.6% of the examined cows (from which more than one third were positive using PCR amplification). Epidemiological studies provided on cattle in Germany, Italy and Turkey reported ten types of BPV (1,2,3,4,6,7,8,9,10,11) [39][40][41][42][43]. In our study, types 1, 3, 6 (mostly related to teat papillomatosis) and 11 were not detected in examined samples.…”
Section: Discussioncontrasting
confidence: 58%
“…The aim of this study was to genetically evaluate the presence and types of BPV associated with teat papillomatosis in Polish cows. This is also the first report of a new putative type of BPV, type 25, and the so called types BPV42 and BPV43 found in teat papilloma lesions in Europe [4]. BPV42 and BPV43 are named as 'so called' types as they have not been classified yet as any particular genus or type and they indicate only a new putative type of isolate name, given by Sauthier et al in their work from 2021 [4].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Trabalho utilizando outras tecnologias, como a amplificação por RCA (replicação por círculo rolante) e sequenciamento de alto rendimento (HTS) em amostras de papilomas de tetos bovinos permitiram a identificação de 11 BPVs conhecidos e 14 BPVs não descritos na literatura (Sauthier et al 2021). Estes resultados demonstram que as técnicas convencionais de diagnóstico podem estar subestimando a diversidade genética desta família viral.…”
Section: Discussionunclassified
“…However, the possibility of a false-negative result cannot be ruled out because formalin fixation may decrease the possibility of BPV detection in tissue samples (De Alcântara et al 2015). Under ideal conditions, the possible presence of BPV should be tested using in situ hybridization (ISH), to correlate the location and distribution of this virus in tissues with cytomorphological alterations (Yaguiu et al 2006), and/or using metagenomic analysis, in order to analyze the infection status and coinfections between different types of papillomaviruses, survey the viral genetic diversity, investigate whether these factors contribute to epidemiological differences in the development of neoplastic lesions (Hu et al 2020, Sauthier et al 2021, and even check the possibility of presence of new viruses (Pastrana et al 2018). Moreover, considering the evidence provided by the works mentioned above, epidemiological data, and the clinical and pathological findings presented here, everything indicates that the possible presence of BPV in the bladder of buffaloes and cattle with EH would have no significance in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%